Dampak Kewarganegaraan terhadap Akses Ekonomi: Analisis atas Kesenjangan Sosial-Ekonomi di Indonesia : The Impact of Citizenship on Economic Access: An Analysis of Socio-Economic Disparities in Indonesia - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Muhammad Huda; Zahra Naila Abhista; Selfia, Selfia (Litera Academica Publishing, 2025)
Citizenship is a legal status connecting individuals to a country, encompassing rights, obligations, identity, and protection. This study evaluates the impact of citizenship status on economic access and socio-economic inequality in Indonesia, focusing on disparities in well-being and economic opportunities. The research employs a normative legal method with approaches including legislation, case studies, conceptual, historical, and comparative analyses. The results show that citizenship inequality creates significant gaps in income, quality of life, and access to services. Individuals with full citizenship have better access to jobs and education compared to those with limited citizenship or no citizenship. This study recommends more inclusive policy reforms to reduce inequality and improve access for individuals with limited citizenship. The findings aim to assist academics and policymakers in designing strategies to enhance community well-being.